Digitalization, sustainable development, and Industry 5.0 : an organizational model for twin transitions - Akkaya, Bülent; Apostu, Simona Andreea; Hysa, Eglantina; Panait, Mirela (Emerald Publishing Limited, 2023)
The business world finds itself in a state of transition, driven in tandem by the strategies of digitalization and sustainable development. A complex process, various stakeholders approach the transition with different tools. Public authorities create the legal and institutional framework, companies fuel the process of technological innovation but also promote sustainable development in their activity. Social responsibility has become a key element of the business strategy also embraced by portfolio investors, universities, consumers. Digitalization, Sustainable Development, and Industry 5.0 offers cutting-edge multidisciplinary research, with expert insights on the technologies and strategies businesses use in the twin transition process. The challenges of a Society 5.0-based new normal organizational model and the contributors' solutions both inform and teach regarding the present, as well as illuminate the path ahead. Understanding the best practices that have emerged in the twin transition allows researchers and practitioners alike to become more effective and serve as a launching point for future generations. The chapters present strategies for academics, researchers, managers, practitioners, and entrepreneurs looking to use new information technologies for business development while protecting the environment. Administrators, educational leaders, policymakers, researchers and other professionals can utilize the extensive research on managing organizations and providing valuable leading and professional development initiatives as well as implementing the latest administrative technologies.